Analisis faktor harga, umur dan pendapatan konsumen terhadap permintaan daging babi pada pasar tradisional Kuala Kurun Kabupaten Gunung Mas - Yemima Yemima; Herlinae Herlinae; - Redianto (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2015)
This study aims to determine the effect of price, age and income of consumers towards pork demand on the Traditional Market Kuala Kurun, districts Gunung Mas. The research data were analyzed using descriptive and correlational method. Results of this study, variable Pricing, Age and Income Consumer simultaneously significantly affect demand for pork in the Traditional Market Kuala Kurun, while partially variable pricing and variable age did not significantly affect demand for pork and variable income impact on the pork demand on Traditional Market Kuala Kurun Key words : Pork, price, consumption, income